Citizen Science for Quantification of Insect Abundance on Windshields of Cars Across Two Continents - Møller, Anders Pape; Czeszczewik, Dorota; Erritzøe, Johannes; Flensted-Jensen, Einar; Laursen, Karsten; Liang, Wei; Walankiewicz, Wiesław (Frontiers in Ecology and Evolution, 2021)
The abundance and the diversity of insects in Europe have declined considerably during recent decades. Here we used citizen science for quantifying the abundance of flying insects on windshields of cars across Europe and Asia. We used the abundance of insects killed against windshields of cars during 3530 transects for a total distance of 83,019 km made by 49 observers as estimates of insect abundance. A total of 124,606 insects were recorded, or approximately 1.5 insect per km. The abundance of insects killed against windshields was highly repeatable among days for the same locality, showing consistent estimates. The main determinants of insect abundance were features of cars (driving speed and car brand that can be considered noise of no biological significance), weather (temperature, cloud cover and wind speed) and time during the season and the day. We tested for differences in the abundance of flying insects killed on windshields of cars predicting and finding (1) a reduction in insect abundance in areas with ionizing radiation at Chernobyl compared to uncontaminated control sites, (2) a reduction in abundance of flying insects in Western compared to Eastern Europe, (3) a reduction in the abundance of flying insects killed on windshields in Europe compared to China, and (4) a difference in abundance of insects killed on windshields of cars in Spain with a significant interaction between Spain and Denmark. Thus a number of abiotic and biotic factors accounted for temporal and spatial heterogeneity in abundance of insects.